Weight change from childhood to adulthood and cardiovascular risk factors and outcomes in adulthood: A systematic review of the literature - Sun Jiahong; Xi Bo; Yang Lili; Zhao Min; Juonala Markus; Magnussen Costan G. (WILEY, 2022)
The magnitude of the associations between life-course change in weight status and health outcomes in adulthood has been inconsistent. This study aims to examine the associations between weight change from childhood to adulthood and cardiovascular disease (CVD) risk factors and outcomes in adulthood. PubMed, Embase and ISI Web of Science between 1 August 1953 and 13 July 2020 were searched, and a total of 52 eligible articles were included. The systematic review supported significant associations between the life-course increase in BMI and high odds of markers in adulthood. In the meta-analyses, normal weight in childhood but excess weight in adulthood or persistent excess weight was associated with increased odds of adult markers. However, those who had excess weight in childhood but were normal weight in adulthood did not have increased odds of nearly all adult markers. This systematic review and meta-analysis suggest that individuals who developed excess weight in adulthood or had excess weight in both periods had higher odds of developing CVD risk factors and outcomes in adulthood. In contrast, the probability of these adult markers could be limited or eliminated for children with excess weight who are able to become adults with normal weight.